Jumping to Conclusions and Its Associations With Psychotic Experiences in Preadolescent Children at Familial High Risk of Schizophrenia or Bipolar Disorder-The Danish High Risk and Resilience Study, VIA 11. (15th July 2022) - Gregersen, Maja; Rohd, Sinnika Birkehøj; Jepsen, Jens Richardt Møllegaard; Brandt, Julie Marie; Søndergaard, Anne; Hjorthøj, Carsten; Knudsen, Christina Bruun; Andreassen, Anna Krogh; Veddum, Lotte; Ohland, Jessica; Wilms, Martin; Krantz, Mette Falkenberg; et al.
Abstract: Background: The jumping to conclusions (JTC) bias, ie, making decisions based on inadequate evidence, is associated with psychosis in adults and is believed to underlie the formation of delusions. Knowledge on the early manifestations of JTC and its associations with psychotic experiences (PE) in children and adolescents is lacking. Design: Preadolescent children (mean age 11.9 y, SD 0.2) at familial high risk of schizophrenia (FHR-SZ, n = 169) or bipolar disorder (FHR-BP, n = 101), and controls ( n = 173) were assessed with the Beads Task to examine JTC. The number of beads drawn before making a decision, "draws to decision" (DTD) was used as a primary outcome. PE were ascertained in face-to-face interviews. General intelligence was measured with Reynolds Intellectual Screening Test. Results: Children at FHR-SZ took fewer DTD than controls (4.9 vs 5.9, Cohen's d = 0.31, P = .004). Differences were attenuated when adjusting for IQ (Cohen's d = 0.24, P = .02). Higher IQ was associated with a higher number of DTD ( B = 0.073, P < .001). Current subclinical delusions compared with no PE were associated with fewer DTD in children at FHR-SZ ( P = .04) and controls ( P < .05). Associations between delusions and DTD were nullified when accounting for IQ. Conclusions: JTC marks familial risk of psychosis in preadolescence, not reducible to general intelligence. JTC is associated with subclinical delusions, but this may be an expression of intellectual impairment. Future studies should establish temporality between JTC and delusion formation and examine JTC as a target for early intervention.